Disaster Risk Reduction and Climate Change Investment in Disaster Education Context - Dahroni, Dahroni; Arozaq, Miftahul; Khoirunisa, Nanda (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Disaster Risk Reduction in Indonesia is an effort that must be done systematically, measurable to achieve national resilience to hydro-meteorological disaster that increases along with climate change. This article examines the forms of risk reduction referring to the global agenda that is Sustainable Development Goals and Sendai Framework Disaster Risk Reduction. This article is more specialized investment framework for disaster risk reduction by the government in reducing the impact of climate change and systematically reducing risk through education. Risk reduction conditions in urban and rural areas show a gap in knowledge context that is superior to urban. However, substantial risk due to climate change occur in rural areas concerned to food security. This lack of knowledge is due to the community, including students, who live in cities have a diverse selection of information and better presentation. Accessibility to this information related to IT infrastructure and socio-economic activities in urban areas of more intensive than in rural areas. Disaster education investments can be systematized through materials and media that support climate change learning according to the spatial context.